Room-temperature ferroelectricity in CuInP2S6 ultrathin flakes - Fucai Liu (Nature Portfolio, 2016)
Two dimensional materials are promising for electronic applications, which await the exploration of cooperative phenomena. Here, Liu et al. report switchable ferroelectric polarization in thin CuInP2S6film at room temperature, demonstrating good memory behaviour with on/off ratio of ∼100 based on two-dimensional ferroelectricity.